1978
DOI: 10.1111/j.1432-1033.1978.tb11998.x
|View full text |Cite
|
Sign up to set email alerts
|

The Structure of Human‐Plasma Low‐Density Lipoprotein B

Abstract: 1. The X-ray small-angle scattering of human plasma lipoprotein B of the low-density fraction ( Q = 1.016-1.060 g . ~m -~) has been recorded to high precision at different electron density contrasts.2. The overall structure of the particles is characterized by a quasi-spherical shape and radial symmetry. A maximum diameter of 23 nm and a molecular weight of 2.4 x lo6 have been determined.3. The internal structure is described in terms of a model consisting of spherical layers with different electron densities … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

1982
1982
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(9 citation statements)
references
References 50 publications
(22 reference statements)
0
9
0
Order By: Relevance
“…The present technology in synchrotron X-ray scattering allows the achievement of highly defined data on dilute particles. As for experiments on LDL particles, X-ray scattering can monitor the structure of the lipid core, of the interfacial shell, and of the protein and phospholipid head groups surface shell (19)(20), without radiation damage effects (21). In Fig.…”
Section: Modified Structure and Reduced Dimension Of Ldl Upon E 2 Binmentioning
confidence: 99%
“…The present technology in synchrotron X-ray scattering allows the achievement of highly defined data on dilute particles. As for experiments on LDL particles, X-ray scattering can monitor the structure of the lipid core, of the interfacial shell, and of the protein and phospholipid head groups surface shell (19)(20), without radiation damage effects (21). In Fig.…”
Section: Modified Structure and Reduced Dimension Of Ldl Upon E 2 Binmentioning
confidence: 99%
“…Experimental evidence and theoretical predictions have offered insights into the structure of apoB and the apoB lipoprotein particles. Early work using calorimetry and x-ray diffraction (Atkinson et al, 1977;Deckelbaum et al, 1977Deckelbaum et al, , 1975Muller et al, 1978), and more recently cryo-electron microscopy (Chatterton et al, 1995a(Chatterton et al, ,b, 1991Gantz et al, 2000;Spin and Atkinson, 1995;van Antwerpen et al, 1997van Antwerpen et al, , 1999, indicated that apoB is located on the surface of a spheroidal lipoprotein particle.…”
Section: Introductionmentioning
confidence: 99%
“…We applied HHP to compare the dynamical behaviour of LDL particles with a healthy normolipidemic composition (N-LDL) to a triglyceride-rich form of LDL (TG-LDL), which mimics pathologically modified LDL. The chemical compositions of LDL particles are well described in the literature2345. Each particle (Fig.…”
mentioning
confidence: 99%